Impact of Angiographic Residual Stenosis on Clinical Outcomes After New‐Generation Drug‐Eluting Stents Implantation: Insights From a Pooled Analysis of the RESET and NEXT Trials. Issue 13 (3rd July 2018) - Watanabe, Hiroki; Morimoto, Takeshi; Shiomi, Hiroki; Natsuaki, Masahiro; Kawai, Kazuya; Kozuma, Ken; Igarashi, Keiichi; Kadota, Kazushige; Tanabe, Kengo; Morino, Yoshihiro; Hibi, Kiyoshi; Akasaka, Takashi; et al.
Abstract : Background: Previous intravascular ultrasound studies suggested the association of stent underexpansion with increased risk of stent thrombosis and restenosis. However, no previous study has addressed the association of the suboptimal angiographic result with target‐lesion revascularization (TLR) in patients receiving new‐generation drug‐eluting stents (DES). Methods and Results: RESET (Randomized evaluation of sirolimus‐eluting versus everolimus‐eluting stent trial) and NEXT (NOBORI biolimus‐eluting versus XIENCE/PROMUS everolimus‐eluting stent trial) are prospective, multicenter, randomized "DES versus DES" trials; 3196 patients and 3235 patients were enrolled in the RESET and NEXT, respectively. Using the pooled individual patient‐level data, the current study population consisted of 3679 patients who received single‐lesion treatment using new‐generation DES such as everolimus‐eluting stent and biolimus‐eluting stent. The study population was divided into 3 groups according to the residual in‐stent % diameter stenosis (%DS) after stent implantation by offline quantitative coronary angiography assessed in a core angiographic laboratory (optimal group: %DS <10%, intermediate group: %DS=10% to 20%, suboptimal group: %DS ≧20%). The cumulative 3‐year incidence of TLR was significantly higher in the suboptimal group than in the intermediate and optimal groups (9.8% versus 5.8% versus 5.7%, log‐rank P =0.004). Even after adjusting for the clinical, angiographic, and procedural characteristics, the excess TLR risk of the suboptimal group relative to the optimal group remained significant (hazard ratio: 1.65, 95% confidence interval, 1.14–2.41, P =0.009). The excess TLR risk of the suboptimal group relative to the optimal group was consistently seen across all the subgroups including heavy calcification. Conclusions: The residual angiographic in‐stent %DS ≥20% was associated with increased risk for TLR in patients treated with the new‐generation DES.